Rice phenolic compounds and their response to variability in growing conditions. Issue 5 (16th August 2020) - Rao, Shiwangni; Santhakumar, Abishek B.; Chinkwo, Kenneth; Snell, Peter; Oli, Prakash; Blanchard, Christopher L.
Abstract: Background and objectives: Phenolic compounds present in rice have substantial antioxidant activity, which has contributed to its potential as a functional food. However, a gap in knowledge exists on how phenolic compounds in rice respond to variation in growing conditions, and the subsequent impact on their antioxidant activity. The current study investigated wholegrain pigmented rice varieties Yunlu29 and Purple, and a nonpigmented variety, Reiziq cultivated in Queensland (QLD) and New South Wales (NSW), Australia. The Queensland location in Mackay had a tropical climate and loamy soil, while the NSW location in Yanco had a temperate climate with clay soil. Findings: Pigmented rice, Yunlu29 and Purple cultivated in Mackay (QLD), exhibited significantly higher total phenolic contents and increased levels of anthocyanin, proanthocyanidin, and antioxidant activity in comparison with Yanco (NSW)‐grown samples. Phenolic compounds including procyanidins and anthocyanidins, cyanidin 3‐glucoside and peonidin 3‐glucoside, were significantly impacted by growing location when compared to other phenolic compounds. For some compounds like vanillic acid, luteolin 4'‐methyl ether 7‐(4G‐rhamnosylneohesperidoside), and proanthocyanidin derivative, the impact of the cultivation environment varied among the three rice varieties, highlighting the influence of both genetics and environment. Conclusions: Cultivation location was found to have a significant impact on phenolic composition and antioxidant activity. It was also observed that phenolic compounds affected by growing location conditions also significantly contributed to antioxidant activity. Significance and novelty: These findings contribute to an understanding of how phenolic compounds respond to the variation in the cultivation environment in Australia, which is essential for breeding high‐value rice varieties with specific phenolic compositions.